Facing the COVID-19 pandemic inside maternities in Brazil: A mixed-method study within the REBRACO initiative - Costa, Maria Laura; Souza, Renato T.; Pacagnella, Rodolfo C.; Bento, Silvana F.; Ribeiro-Do-Valle, Carolina C.; Luz, Adriana G.; Lajos, Giuliane J.; Nobrega, Guilherme M.; Griggio, Thayna B.; Charles, Charles M.; Tedesco, Ricardo P.; Fernandes, Karayna G.; et al. (Public Library of Science (PLoS), 2021)
Introduction COVID-19 pandemic posed major challenges in obstetric health care services. Preparedness, development, and implementation of new protocols were part of the needed response. This study aims to describe the strategies implemented and the perspectives of health managers on the challenges to face the pandemic in 16 different maternity hospitals that comprise a multicenter study in Brazil, called REBRACO (Brazilian network of COVID-19 during pregnancy). Methods Mixed-method study, with quantitative and qualitative approaches. Quantitative data on the infrastructure of the units, maternal and perinatal health indicators, modifications on staff and human resources, from January to July/2020. Also, information on total number of cases, and availability for COVID-19 testing. A qualitative study by purposeful and saturation sampling was undertaken with healthcare managers, to understand perspectives on local challenges in facing the pandemic. Results Most maternities early implemented their contingency plan. REBRACO centers reported 338 confirmed COVID-19 cases among pregnant and post-partum women up to July 2020. There were 29 maternal deaths and 15 (51.8%) attributed to COVID-19. All maternities performed relocation of beds designated to labor ward, most (75%) acquired mechanical ventilators, only the minority (25%) installed new negative air pressure rooms. Considering human resources, around 40% hired extra health professionals and increased weekly workload and the majority (68.7%) also suspended annual leaves. Only one center implemented universal screening for childbirth and 6 (37.5%) implemented COVID-19 testing for all suspected cases, while around 60% of the centers only tested moderate/severe cases with hospital admission. Qualitative results showed that main challenges experienced were related to the fear of the virus, concerns about reliability of evidence and lack of resources, with a clear need for mental health support among health professionals. Conclusion Study findings suggest that maternities of the REBRACO initiative underwent major changes in facing the pandemic, with limitations on testing, difficulties in infrastructure and human resources. Leadership, continuous training, implementation of evidence-based protocols and collaborative initiatives are key to transpose the fear of the virus and ascertain adequate healthcare inside maternities, especially in low and middle-income settings. Policy makers need to address the specificities in considering reproductive health and childbirth during the COVID-19 pandemic and prioritize research and timely testing availability.